Special Features of Self-Access English Learning Pandemic Modules - Reswari, Cinthia; Mokhamad Sabil Abdul Aziz (CV. Kalimasada Group Profesional, 2024)
In the Covid-19 pandemic, the Indonesian Ministry of Education and Culture developed special English self-access learning modules for grade IX students. These modules are intended to facilitate the students in studying English at home by themselves. There are special features in these modules that are especially provided for the students. These special features are worth to be investigated. The aim of this research is to explain the special features provided by the writers in the self-access English learning modules. This research is a content analysis research. It is found that there are five special features in these modules. These special features include 1) detailed objectives of each unit, 2) roles of the teacher and parents table, 3) Indonesian translation for the instructions, 4) graded scaffolding activities, and 5) detailed answer keys. Hopefully, this research would give new insights upon self-access English learning materials especially for special nationwide conditions.